ANALISIS PENGARUH LITERASI KEUANGAN DAN MOIVASI TERHADAP MINAT BERINVESTASI DI PASAR MODAL STUDI KASUS PADA MASYARAKAT DI PROVINSI RIAU - rosyidah, Alfianti rosyidah; Andi Afrizal (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to determine the effect of financial literacy and motivation on interest in investing in the capital market (case study of people in Riau Province). The research method used is quantitative method with descriptive approach. The population in this study were people in Riau Province. The technique used in sampling is using Non Probability Sampling with Purposive Sampling technique with a total sample of 100 respondents. Data collection was carried out by distributing questionnaires to a predetermined sample via google form. The data analysis technique in this study uses descriptive analysis and quantitative analysis and in the data processing process uses the help of IBM SPSS software for windows version 22. The results of this study indicate that, based on the t test, financial literacy and motivation partially have a significant and positive effect on investment interest. While based on the f test shows that financial literacy (X1) and motivation (X2) simultaneously have a significant effect on investment interest in the capital market.